Predictors Of Capital Expenditures in Regency/City Regional Government in West Java Province 2017-2022 - Endayani, Fitri; Kartika Berliani (Universitas Indonesia Membangun, 2023)
This research aims to analyze the influence of Regional Original Income, Budget Surplus, and Profit-Sharing Funds on Capital Expenditures. Capital expenditure is important for regional governments to improve the welfare of their people because it has objectives related to public services, one of which is to obtain fixed assets such as equipment, buildings, infrastructure, and other fixed assets. Things that influence the absorption of capital expenditure effectively or not can be seen from the Budget Realization Report. This research method is quantitative research with a descriptive and verification approach. Based on the research results, it was found that (1) Regional Original Income has an influence but is not significant on Capital Expenditures (2) Budget Surplus does not have a significant influence on Capital Expenditures (3) Profit-Sharing Funds do not have a significant influence on Capital Expenditures. The implication of this finding is that these three factors do not significantly influence Capital Expenditures. However, it should be noted that the influence of Regional Original Income on Capital Expenditures still needs to be researched further to ascertain whether this influence is truly insignificant or only occurs in certain cases.